Albumin Naskapi variant in North American Indians and Eti Turks. - Franklin, S G (1980)
Both conventional polyacrylamide gel electrophoresis and a new type of electrophoretic screening procedure indicate that the polymorphic albumin variants Naskapi, found chiefly in the Naskapi Indians of Quebec, and Mersin, found in the Eti Turks of southeastern Turkey, are molecularly identical or very similar and that the amino acid substitution site in these variants is located between residues 330 and 446. This discovery is consistent with a genetic relationship between the Eti Turks and American Indians. We also report a new variant found in the Eti Turks, albumin Adana, which migrates similarly to albumin B on conventional gels but which our new system shows to differ from the common albumin A and albumin B by a substitution between residues 549 and 585.